1999
DOI: 10.1002/(sici)1096-8628(19990903)86:1<1::aid-ajmg1>3.3.co;2-1
|View full text |Cite
|
Sign up to set email alerts
|

Partial monosomy of distal 10q: Three new cases and a review

Abstract: We report on 3 patients with partial deletions of the long arm of chromosome 10-46,XY,del (10)(q26.2), 46,XX,del(10) (q25.3q26.3) or 46,XX,del(10)(q26.1), and 46,XX,del (10)(q26.1). They are compared with other known cases with interstitial or terminal deletions involving chromosome bands 10q25 or q26. Unique manifestations are identified, including scoliosis and a severe behavior disorder with attention deficit and hyperactivity in a 12-year-old boy as well as patchy alopecia in a 6-year-old patient.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
26
0

Year Published

1999
1999
2009
2009

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(29 citation statements)
references
References 17 publications
3
26
0
Order By: Relevance
“…The typical features associated with these deletions include a prominent, beaked nose, malformed ears, mental retardation, cardiac defects, and anogenital malformations. 25 The features of the patient reported here do not overlap with this reported phenotype, giving more credence to the likelihood that his deletion is not related to his phenotype.…”
Section: Discussionsupporting
confidence: 53%
“…The typical features associated with these deletions include a prominent, beaked nose, malformed ears, mental retardation, cardiac defects, and anogenital malformations. 25 The features of the patient reported here do not overlap with this reported phenotype, giving more credence to the likelihood that his deletion is not related to his phenotype.…”
Section: Discussionsupporting
confidence: 53%
“…23 One was a 6 year old, moderately delayed female with an additional trisomy of 16qter owing to a familial t(5;16) and mild dysmorphic features (dense hair, prominent forehead, large mouth, thin upper lip, and thick lower lip) and normal growth. The same group reported another unrelated 12 year old female with a similar deletion 5qter and duplication 16qter, but this time de novo, and a lownormal IQ (80)(81)(82)(83)(84)(85)(86)(87)(88)(89), normal growth, mild facial dysmorphism (mild epicanthic folds, upward slanting palpebral fissures, low nasal bridge, short philtrum), slender hands and feet, cardiac abnormalities (mild pulmonary valve stenosis and large VSD), and vesicoureteric reflux.…”
Section: Qmentioning
confidence: 99%
“…The vast majority of studies have reported terminal deletions, with breakpoints ranging from 10q23.3 to 10q26.3 as determined by conventional cytogenetic techniques, and only a few cases of 10q interstitial deletions have been previously identified (1)(2)(3)(4)(5). The vast majority of studies have reported terminal deletions, with breakpoints ranging from 10q23.3 to 10q26.3 as determined by conventional cytogenetic techniques, and only a few cases of 10q interstitial deletions have been previously identified (1)(2)(3)(4)(5).…”
mentioning
confidence: 99%